2019
DOI: 10.1108/gkmc-02-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of South African universities and communities archives

Abstract: Purpose The purpose of this study to investigate the relationships between South Africa (SA) universities and universities surrounding communities (USC) for preserving community histories and serve the universities’ mandate to support their local communities and support universities’ teaching and scholarship. Design/methodology/approach The study used a multiple case study approach through interviews. The population of the study comprised representatives from selected universities and their USC. Findings T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The study conducted by Segaetsho and Mnjama (2012) indicated that the preservation of archival materials in Africa has not received adequate attention. The lack of preservation strategy contributed to ineffective collaboration between records and archives and student affairs divisions to preserve records and prevent loss of records (Wagner & Smith, 2012;Samuels 1992;Mnjama, Mooko &Manewe-Sisa 2016;Segaetsho & Mnjama 2012;Millar 1997;Ambira & Kemoni 2011;Erima & Wamukoya 2012;Netshakhuma 2019a;2019b;2019c;2019d). Few studies have examined student affairs records preservation strategies (Kezar 2003).…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by Segaetsho and Mnjama (2012) indicated that the preservation of archival materials in Africa has not received adequate attention. The lack of preservation strategy contributed to ineffective collaboration between records and archives and student affairs divisions to preserve records and prevent loss of records (Wagner & Smith, 2012;Samuels 1992;Mnjama, Mooko &Manewe-Sisa 2016;Segaetsho & Mnjama 2012;Millar 1997;Ambira & Kemoni 2011;Erima & Wamukoya 2012;Netshakhuma 2019a;2019b;2019c;2019d). Few studies have examined student affairs records preservation strategies (Kezar 2003).…”
Section: Problem Statementmentioning
confidence: 99%
“…Students interact with communities surrounding universities on community projects and sponsorships. According to Chung (2018) and Netshakhuma (2019c;2019d;2020), institutions should be accountable to society by creating and retaining knowledge via records and archives.…”
Section: Collaboration Between Student Affairs and Records And Archivmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALM function provides a pivotal space for negotiating meaning about past histories, reconstructions of cultural memory and reinterpretation of culture (Anderson, 2005: 15). The KNP ALM are the product of historical struggle as they are sources of the history of the development of the park (Netshakhuma 2019h). SHRC provided a wealth of information about the development of the park.…”
Section: History Of South African National Parksmentioning
confidence: 99%
“…According to Satgoor (2015: 104) and Netshakhuma (2019h) there is wide-scale cognisance that the best way to address and support the transformation of ALM functions into community hubs is for the organisation to invest in staff development and training.…”
Section: Literature Reviewmentioning
confidence: 99%